2014
DOI: 10.1109/tvcg.2014.2346320
|View full text |Cite
|
Sign up to set email alerts
|

Four Experiments on the Perception of Bar Charts

Abstract: Bar charts are one of the most common visualization types. In a classic graphical perception paper, Cleveland & McGill studied how different bar chart designs impact the accuracy with which viewers can complete simple perceptual tasks. They found that people perform substantially worse on stacked bar charts than on aligned bar charts, and that comparisons between adjacent bars are more accurate than between widely separated bars. However, the study did not explore why these differences occur. In this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 12 publications
7
83
0
Order By: Relevance
“…For both, linear and radial separate charts, we found that users underestimated value differences. This reinforces that lengths comparisons are easier when the bars are horizontally aligned, thereby confirming previous results [15,31,47,50].…”
Section: ×12-hours Vs 1×24-hours Chartsupporting
confidence: 90%
“…For both, linear and radial separate charts, we found that users underestimated value differences. This reinforces that lengths comparisons are easier when the bars are horizontally aligned, thereby confirming previous results [15,31,47,50].…”
Section: ×12-hours Vs 1×24-hours Chartsupporting
confidence: 90%
“…Task Completion: The lower rating for Task 1 is little surprising, as it is difficult to precisely compare the length of bars that are not aligned, i.e., have varying start and end points [31]. For that reason, the expert users could have solved Task 1 more efficiently with a simple SQL statement than with the visualization.…”
Section: Resultsmentioning
confidence: 99%
“…There is a body of work that specifically investigates the perception of bar charts. Talbot et al have taken Cleveland and McGill's study and delved deeper into the questions of how different bar chart configurations impact accuracy [TSA14].…”
Section: Related Workmentioning
confidence: 99%
“…The charts display three values each, labeled A, B, and C for reference in the questions. We constrain the bars to three to contain the scope of the study to issues caused directly by the embellishments, avoiding compound issues that may appear when two compared bars have many bars between them (as found by Cleveland and McGill [CM84] and Talbot et al [TSA14]). The minimum value on the y‐axis always starts at 0, while the maximum y‐axis value is capped at 100.…”
Section: Studymentioning
confidence: 99%